Pengaruh Lingkungan Kerja dan Komunikasi terhadap Kinerja Karyawan Melalui Kerjasama Tim - Noure, To Varel Rahma; Candana, Dori Mitra; Azka, Bayu Pratama (Politeknik Baubau, 2025)
This study aims to test the influence of the work environment and communication on employee performance through teamwork by using primary data obtained by distributing questionnaires to 33 employees as respondents, namely at JNE Main Branch Office, Nipah. In this study, Structural Equation Modeling (SEM) analysis tool was used using Partial Least Square (PLS). The results showed that the work environment had a positive and insignificant effect on teamwork. Communication has a positive and significant effect on teamwork. The work environment has a positive and significant effect on employee performance. Communication has a positive and insignificant effect on employee performance. Teamwork has a positive and insignificant effect on employee performance at JNE Nipah Main Branch Office. The work environment through teamwork has a positive and insignificant effect on employee performance. Communication through teamwork has a positive and significant effect on employee performance at JNE Main Branch Office, Nipah. The R-Square value for the teamwork variable was 0.534, which means that 53.4% of the teamwork variables were influenced by the variables of the work environment and communication, while the remaining 46.6% were influenced by other variables outside of this study. Then the R-Square value for the employee performance variable was 0.426, meaning that 42.6% of the employee performance variables were influenced by the variables of the work environment, communication, and teamwork, while the remaining 57.4% was explained by other variables outside of this study.